Numeric Study of the Influence of the Signal Noise, Location of the Sensors and Sampling Rate on the Strain-Only Bwim Method - Lobo Aguilar, Sergio (2025)
Bridge Weigh-In-Motion (BWIM) systems have been used successfully to identify some of the properties of the trucks that travel over a highway. However, is not always easy to control the sources of uncertainty and therefore the reliability of the results might be affected. In this research, the effect of possible experimental difficulties on the BWIM method based on strain measurements was studied. In particular, three effects were analyzed: the noise level present on the signal, the location of the sensors on the bridge and the sampling rate used for data acquisition. These effects were modeled numerically by adding synthetic noise to an idealized wave response. The results are discussed with focus on the possible consequences on the estimation of velocities and gross vehicle weight of truck during field tests.